FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022) - Winarti, Irma; Romadon, Ahmad Sahri (STIE PENA, 2024)
This research aims to test the influence of independent variables, namely firm size (X1), leverage (X2), and profitability (X3) on the dependent variable, namely company value (Y) in food and beverage companies listed on the Indonesia Stock Exchange in 2020- 2022. The sample used in this research was 20 companies selected using purposive sampling techniques. The analytical method used is the multiple linear regression analysis method which was tested using the SPSS 24 program application. The results of this research show that company size has no effect on company value, leverage has a negative effect on company value and profitability has a positive effect on company value. Keywords:Frim Size, Leverage, Profitability, Company Value